Wealth, Calling, and Equality: The Perception of Religious Socio-Economic Concepts among Baptists and Orthodox Christians - Alexander Khlevov; Alina Ivakina; Dmitry Mayevsky; Alexander Smal (Journal of Economic Sociology, 2024)
This article attempts a comparative analysis of the socio-economic attitudes of the Orthodox and Protestants of the city of Sevastopol. The problem of the study is the difficulty in understanding how, in modern socio-economic conditions, the patterns of behavior prescribed by the church are fulfilled in practice. The main purpose of this study is to identify and analyze the attitude of believers toward socio-economic attitudes (such as attitudes towards wealth, vocation, and equality) dictated by the concepts of the Russian Orthodox Church and the Evangelical Christian Baptist movement. The research is based on the formal sociology of G. Simmel, as well as on modern sociological and religious studies. Evangelical Christian Baptist communities were chosen as the most widespread denomination of Protestantism in the city of Sevastopol. 33 structured interviews were conducted with representatives of two faiths: Orthodox and Protestants (Evangelical Christians-Baptists). The study identified the main socio-economic attitudes of Orthodox and Baptists, which were correlated with the cultural characteristics of Russian society and with the socioeconomic concepts of both churches. The facts in the history of Orthodoxy and the Baptist branch of Protestantism that influenced the adoption of certain doctrinal and socio-theological positions were also described. In addition, the analysis of materials concerning the specifics of the modern life of Evangelical Christians-Baptists and Orthodox Christians has been carried out.